APPLICATION OF POWER POINT SOFTWARE IN JAPANESE TEACHING TO IMPROVE TEACHING QUALITY - Tan, Hoi Huynh (International Journal of Psychosocial Rehabilitation, 2020)
The role and effectiveness of applying information technology in teaching has been proved by domestic and foreign educational practices in recent years, it shows that the application of information technology in teaching and learning is a trend. Inevitability of education. Power point lectures are one of the most effective supportive tools for teachers to make their lessons easier and more attractive. Because a lecture with technology applications must show science and pedagogy, requires teachers to have professional knowledge, pedagogy and information technology skills. This article refers to Japanese as a subject of social science, so knowledge is sometimes very abstract and difficult to understand, if not illustrated by models, image diagrams, it is difficult for students to acquire new knowledge. The use of technology in teaching certainly brings a lot of benefits in imparting knowledge to students.